A Review of Rural Development and Poverty Amelioration Programmes in Niyamatabad Block, District Chandauli - Tiwari, P. K. (National Geographical Journal of India, 2022)
Poverty is chronic and multi-dimensional in nature in India. It is concentrated in the rural areas of certain states as well as in certain social groups. Rural poor have identifiable occupational structure concentrating specially in agricultural labour and artisanal households group in rural areas. Rural poverty is now multiplied with the population explosion and unemployment situation. A number of rural development programmes has been launched in the Five Years Plans to raise income, provide employment, make masses literate and alleviate the poverty of rural poor in the country. This paper evaluates different rural development programmes implemented in the study area